2013
DOI: 10.1074/jbc.m113.470450
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dynamic Soluble Surfactant-induced Amyloid β Peptide Aggregation Intermediates

Abstract: Background: ␤-Structured oligomers of the amyloid ␤ peptide are considered neurotoxic and on-pathway to amyloid fibril formation. Results: Surfactant-induced co-aggregated oligomers show dynamic rapid exchange with free peptide during a slow fibril formation process. Conclusion: ␤-Structure inducing small molecules kinetically promote peptide assembly into co-aggregates. Significance: Knowledge about molecular mechanisms of peptide aggregation modulators is potentially helpful for therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 67 publications
7
30
0
Order By: Relevance
“…In earlier studies by others, 0.2% SDS was reported to induce globular aggregates of Aβ; moreover, no fibrils were detected by atomic force microscopy (34). Our findings are consistent with those of others, who found that SDS initially induced globular aggregates of Aβ, which later assembled spontaneously into fibrils (35).…”
Section: Discussionsupporting
confidence: 92%
“…In earlier studies by others, 0.2% SDS was reported to induce globular aggregates of Aβ; moreover, no fibrils were detected by atomic force microscopy (34). Our findings are consistent with those of others, who found that SDS initially induced globular aggregates of Aβ, which later assembled spontaneously into fibrils (35).…”
Section: Discussionsupporting
confidence: 92%
“…In Aβ 40 the Zn 2+ ion is coordinated by four ligands, the histidines H6, H13, and H14 and the N-terminal D1 (15). Interaction between Zn 2+ and Aβ 40 causes NMR signal loss of the N-terminal residues (15,17), and these data suggest that NMR signal loss may be attributed to a chemical exchange process on an NMR intermediate time scale (18) as reported for similar exchanging systems (19)(20)(21).…”
mentioning
confidence: 52%
“…By using those animals in the present study, we also found that intracellular bA was decreased following both time intervals of CDK5 silencing treatment in contrast to extracellular bA plaques, APP processing, and bA1-40/ 1-42 production, which were decreased only with shortterm treatment. This result suggests that CDK5 knockdown is relevant in the reversion of bA protein levels and for intra-and extracellular b-amyloidosis in older 33 Tg-AD mice for a shorter treatment period, given that soluble bA (bA1-40) is also involved in the pathogenesis of AD (Haass and Selkoe, 2007;Benilova et al, 2012, Abelein et al, 2013. This finding also suggests that, in a mode independent of this histopathological hallmark, CDK5 reduction downregulates insoluble tau and improves learning and memory with long-term treatment despite the recovery of basal enzymatic activity at 1-year postinjection.…”
Section: Discussionmentioning
confidence: 95%